Curriculum Innovation in Islamic Religious Education: Balancing Sharia Principles with Global Educational Standards - Muhammad Irsyad Baitussalam (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
Curriculum innovation is essential in Islamic religious education to balance adherence to Sharia principles with global educational standards. This study explores how curriculum design—including Sharia integration, alignment with international benchmarks, pedagogical innovation, and assessment strategies—affects students’ cognitive, practical, and moral development. Employing a qualitative approach with interviews and focus groups involving educators and curriculum developers, the study reveals that Sharia integration most strongly influences moral and ethical grounding, while alignment with global standards enhances academic competitiveness. Pedagogical innovation and assessment strategies further support engagement, critical thinking, and accountability. Findings underscore the importance of a holistic, balanced curriculum that produces graduates who are morally responsible, academically competent, and globally prepared.